2012
DOI: 10.1159/000342148
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cortical Vessel Signs on Susceptibility-Weighted Images after Full Recanalization in Hyperacute Ischemic Stroke

Abstract: Background: The cortical vessel signs (CVSs) on susceptibility-weighted images (SWIs) have been reported in patients with hyperacute ischemic stroke. We evaluated the change of this susceptibility sign on the immediate SWI after full recanalization and its clinical implications. Methods: Nineteen hyperacute ischemic stroke patients who had acute large artery occlusion and underwent post-recanalization SWI were enrolled in this study. The patients had ICA (internal carotid artery, 2 cases), M1 (M1 segment of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 42 publications
1
75
1
Order By: Relevance
“…[1][2][3] Susceptibility-weighted imaging is useful for evaluating cerebral veins in AIS because it is extremely sensitive to paramagnetic substances such as deoxyhemoglobin, thus reflecting the oxygen extraction fraction and the cerebral metabolic rate of oxygen of the hypoxic tissue. [1][2][3][4] Shortly after vascular occlusion, the uncoupling between oxygen supply and demand in the hypoperfused region leads to an elevated oxygen extraction fraction and subsequent increased level of deoxyhemoglobin in the vessel, which contributes to prominent hypointensity of the draining veins on SWI. [5][6][7] Asymmetric cortical veins, which can be visualized on SWI after AIS and are considered an indicator of salvageable ischemic penumbra, were found to be associated with 3-month outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Susceptibility-weighted imaging is useful for evaluating cerebral veins in AIS because it is extremely sensitive to paramagnetic substances such as deoxyhemoglobin, thus reflecting the oxygen extraction fraction and the cerebral metabolic rate of oxygen of the hypoxic tissue. [1][2][3][4] Shortly after vascular occlusion, the uncoupling between oxygen supply and demand in the hypoperfused region leads to an elevated oxygen extraction fraction and subsequent increased level of deoxyhemoglobin in the vessel, which contributes to prominent hypointensity of the draining veins on SWI. [5][6][7] Asymmetric cortical veins, which can be visualized on SWI after AIS and are considered an indicator of salvageable ischemic penumbra, were found to be associated with 3-month outcome.…”
mentioning
confidence: 99%
“…On the basis of SWI, it was demonstrated that prominent hypointense cortical veins and medullary veins predicted infarct growth and poor outcome after AIS. 2 However, most of the included patients did not undergo revascularization therapy, and salvage of potentially penumbral regions was therefore unlikely. The imaging was also acquired up to 72 hours after AIS, which limits its applicability to hyperacute treatment decision-making.…”
mentioning
confidence: 99%
“…7,59 SWI can effectively determine the CVS to detect arterial occlusion 49 and the change in CVS preand postadministration of the thrombolytic agent to assess reperfusion levels. 7 Although CVS measurements offer precise information on the thrombotic region, a simpler detection method involves the presence of dilated and hypointense cortical vessels on SW images.…”
Section: Thrombosis Detectionmentioning
confidence: 99%
“…7,59 SWI can effectively determine the CVS to detect arterial occlusion 49 and the change in CVS preand postadministration of the thrombolytic agent to assess reperfusion levels. 7 Although CVS measurements offer precise information on the thrombotic region, a simpler detection method involves the presence of dilated and hypointense cortical vessels on SW images. 97 The dilated region on SWI correlates with MR angiography (MRA) findings 93 and could be used to monitor occlusion, 57 along with the possibility for hemorrhagic transformation, 57,64 over time.…”
Section: Thrombosis Detectionmentioning
confidence: 99%
See 1 more Smart Citation